GAMBARAN PENGETAHUAN IBU TENTANG PENURUNAN NYERI PERSALINAN MENGGUNAKAN TEKNIK NAPAS DALAM - Rina Astuti; Sri Legawati (Jurnal Keperawatan Dan Kesehatan Holistik, 2025)
Deep breathing technique is one type of breathing technique, and can reduce pain in mothers in labor non-pharmacologically by taking a deep breath during contractions using diaphragmatic breathing through the nose so that the abdomen is lifted slowly, the chest expands fully will flow oxygen to the blood which is then distributed throughout the body will release endorphin hormones which are natural pain relievers in the body. This study uses a "Descriptive Survey" research design and this research method is Cross Sectional with an approach. The population in this study was 160 families in Dusun II, Pasiran Village, using the Simple Random Sampling technique with a sample size of 20 respondents. Data collection techniques by observation, interviews, documentation, and filling out questionnaires and using the categories know and do not know. From the results of this study, the results obtained about the description of maternal knowledge about reducing labor pain using deep breathing techniques are said to be in the "Good" category where the score is 13 with a presentation of 86.6%. The conclusion of the study is that deep breathing techniques can reduce pain in mothers in labor. It is expected that mothers who have experience giving birth, when accompanying mothers giving birth, teach mothers according to their experience how to deal with labor pain so that mothers who do not have experience do not feel afraid.